A prospective comparison of the operative outcome of D1 and modified D2 gastrectomy in adenocarcinoma of the stomach - Tusar Kanti Saradar,; Jorge Pal,; Gautam Ghosh,; Bikash Chandra Ghosh, (Asian Journal of Medical Sciences, 2022)
Background: Gastric adenocarcinoma is a leading cause of cancer and cancer related death among Asian countries. Although there is considerable improvement in chemoradiation, surgery still remains the primary curative modality with special emphasis on lymphadenectomy. Aims and Objectives: The aim of the study was to assess and compare post-operative morbidity and mortality, anastomotic dehiscence, and length of hospital stay between D1 and modified D2 gastrectomy in adenocarcinoma of the stomach. Materials and Methods: A prospective, open labeled, and comparative analysis was done in patients with adenocarcinoma of stomach at a tertiary care hospital in Eastern India for 15 months. Total (n=50) patients were divided into two groups and undergone D1(n=24) and modified D2 gastrectomy (n=26) operation, respectively. Post-operative assessment was done for 6 months following the operations. Results: In the study, (n=35) patients presented with antral growth of which 18 (51.4%) patients underwent D1and 17 (48.6%) patients modified D2 gastrectomy. Most of the Stage III cases were dealt by modified D2 surgery (62.5%) whereas Stage I by D1 surgery (68.2%). Incidences of hematemesis noted around 9 (34.6%) in D1 group patients and lesser in modified D2 group 6 (25%) with P=0.545. However, the incidences of melena were observed that more 11 (45.8%) in modified D2 group in the study patients was compared to D1 group 6 (23.0%) which was statistically insignificant (P=0.130).Post-operative complication (mainly wound dehiscence) was more in D1 surgery group 12 (46.1%) as compared to modified D2 group 8 (33.3%) and the finding was statistically insignificant (P=0.399). There were 4 (33.3%) cases of mortality in modified D2 group as compared to 8 (66.7%) cases in D1 group.The duration of hospital stays,that is,>14days was observed longer in the modified D2 surgery cases as compared to the other group (<8 days)and this difference was statistically very significant (P<0.001). Conclusion: Outcome of modified D2 operation in adenocarcinoma of stomach is better than D1 gastrectomy with lesser post-operative morbidity and mortality with longer duration of hospital stays and possibly a better chance of survival.